Contribution of honeybees to soybean yield - Blettler, Diego César; Fagundez, Guillermina Andrea; Caviglia, Octavio (Springer, 2018)
Despite the economic importance of soybean [Glycine max (L.) Merr.], knowledge on the contribution of entomological pollination on seed yield is scarce. This study estimates the production of soybean resulting from pollination by honeybees (Apis mellifera L.) in two consecutive growing seasons in Paraná (Argentina). Experiments had two treatments: excluded flower-visiting insects (EV) and non-excluded flower-visiting insects (NEV). The abundance of honeybees was similar in both years, although soybean production differed significantly (P < 0.05) between years. The NEV treatment out-yielded (P < 0.001) the EV treatment by 18% (5224 vs. 4415 kg ha−1) in year 1, which was associated with an increase in the seeds per unit area but not with individual seed weight. In contrast, seed yield (on average 3830 kg ha−1) and seeds per unit area did not differ between treatments in year 2. Individual seed weight was 3–5% (P < 0.05) higher in EV than in NEV in both years. The mechanisms involved in the seed yield increase could be related with pollen sterility in relegated flowers in secondary racemes or in distal locations of primary racemes under favorable conditions, as recorded in year 1. Thus, the action of honeybees carrying pollen from fertile flowers to relegated flowers may have increased the pod and seed set in treatment NEV in year 1.